Microsoft Sway on Student Digital Literacy in Postcovid-19 - Rulviana, Vivi; Dayu, Dian Permatasari Kusuma (Proceedings International Conference on Education Innovation and Social Science, 2022)
Microsoft Sway media is a presentation tool created and played online on the sway.com page. This study aims to determine the effectiveness of Microsoft 365: sway media on students' digital literacy in online learning in the era of society 5.0. This research is a quasi-experimental design (quasi-experiment). The form of this research design is the Nonequivalent Control Group Design. The population in this study were students of the University of PGRI Madiun. The sampling technique in this study used a purposive sampling technique. The sample is 60 students in the experimental class and 60 in the control class. The types of instruments used in this research are essays and response questionnaires. Hypothesis testing in this study uses a t-test. The results showed that the Microsoft 365: sway media, applied in the experimental class, was very effective for students' digital literacy.